(untitled) (Eurasian Research Bulletin, 2023)
In this scientific article, the definitions of the term "green economy" given by scientists of the world and our country are brought into one system and explained. The content, essence and necessity of the theory of "green economy" are revealed. The level of importance and relevance of "green economy" in Uzbekistan is shown on the basis of regulatory and legal documents. At the same time, the impact of "green economy" on industries and sectors and its necessity are shown. At the same time, the theoretical foundations and practical importance of "green economy" in the education system of our country, as well as the trend of development, have been scientifically substantiated